CEASA : a organização do abastecimento de alimentos e a desigualdade em Uberlândia - MG (1978-2009) - Moraes, Mário (2015)
This study approaches the experiences of the Distribution Centre workers atUberlândia city, taking their memories to form a conducting wire in the direction of dialectical process that enabled the construction of Uberlandia s CEASA, in 1978. Oral sources led us to think the conditions experienced by childrenlooking forfood in the 70 s at public spaces of the city. The press was a field where conflicts engendered stereotypes about the poor, based on hegemonic groupsvalues, in order to set limits for workers.The creation of Uberlandia sDistribution Centre in conjunction with the creation of other institutions aimed to discipline the poor spresence in the most noble and visible places ofthe town. The main objective presented to justify the CEASA screation was to move the transit of food transport vehicles to the margins of the city. During the research, we found another objective of equal importance in displacement of own social struggle, with the removal of poor children and beggars who bothered in the people at the markets and the Municipal Market. In the CEASAwe can understand the experiences of the workers seeking to improve the material living conditions facing many dangers of occupational accidents, in the midst of a struggle for rightsprocess. Furthermore, we still can see that, three decades after the Distribution Centre creation, the presence of poor children looking forfood wastage will continue strong and it will motivate new official containment measures such as the creation of the Food Bank Program, with proposes food s donationfor poor families directly in their own neighborhoods.